A Doubter’s Guide to Law and Natural Rights - Allan, James (Victoria University of Wellington Law Review, 1998)
The assertion that there are no independent moral values which transcend the view of an individual, or the society in which he or she lives, may cause consternation to many. Indeed it has been argued that it will tum the liberal western legal tradition on its head by removing the foundation for the rights on which that tradition is built. James Allan in this article suggests that such consternation is misplaced. While an objective moral reality is denied, he accepts the existence of an objective physical world. From this premise he reasons that certain courses of conduct will have certain consequences which, by human nature rather than moral precept, will be desirable or undesirable. It is therefore unlikely that the status quo need be changed to take account of the possibility of moral scepticism. The author proceeds to argue that if the fiction of moral realism were exposed it is likely that the position of tolerance widely adopted in the West would be able to be better defended. He concludes that the Western legal tradition, its commitment to tolerance and the existence of rule based rights would be preserved and enhanced by an acceptance of moral scepticism.